Echocardiography quiz: Peculiar left ventricular outfl ow tract masses causing dynamic outfl ow obstruction - Liebenberg, J.J.; Doubell, A.F.; Herbst, P.G. (SA Heart Journal, 2017)
Evaluation of left ventricular outflow tract (LVOT) masses.